Kajian Teori Pemikiran Ekonomi Mazhab Klasik dan Relevansinya pada Perekonomian Indonesia - Atmanti, Hastarini Dwi (JEB17 : Jurnal Ekonomi dan Bisnis, 2017)
AbstractThe classical school of liberalism, born in the eighteenth century to the middle of the nineteenth century, states that government intervention is kept to a minimum in the economy (laissez faire laissez passer), since interference actually causes distortion. The economy has the ability to return to the balance position automatically. Classical adherents such as Adam Smith, Jeremy Bentham, Thomas Robert Malthus, Robert Owen, David Ricardo, Jean Baptiste Say, Antoine Augustine Cournot and John Stuart Mill, believe that the free market system will bring about an efficient level of economic activity over the long term. Full employment will always be achieved and the economy will experience steady growth.Â Keywords: classical school, laissez faire laissez passer, efficient economic activityJEL classification: B12, B21